The Effectiveness of Monetary Policy Towards Stock Index Case Study : Jakarta Islamic Index 2006-2014 - el Hasanah, Lak lak Nashat; Panjawa, Jihad Lukis (Universitas Muhammdaiyah Surakarta, 2016)
Fluctuation in economy situation is an important indicator for investor decision making. The investor actions are base on the minimum risk while having maximum profit. One of it is observing the condition of macro variables within monetary policy. This research aims to analyze the impact of inflation, money supply, exchange rate, and birate towards stock of jakarta islamic Index. The type data used is times series periode 2006-2014. Multiple linier regression with chow test and dummy variable approach to compare and to know the behavior of each independent variables. The result shows partially that birate and exchange rate negatively impact Jakarta Islamic Index before global monetary crisis in 2008, while inflation and money supply not that significantly impact. After global monetary crisis in 2008, partially, birate variable and money supply significantly giving positive influence to Jakarta Islamic Index, while at same time exchange rate and inflation are not significantly influencial. Simultaneously, inflation, money supply, exchange rate, and birate influence Jakarta islamic Index.